Similar Inhibition of Dynamic Adhesion of Lymphocytes From IBD Patients to MAdCAM-1 by Vedolizumab and Etrolizumab-s - Binder, Marie-Theres; Becker, Emily; Wiendl, Maximilian; Schleier, Lena; Fuchs, Florian; Leppkes, Moritz; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2018)
Background: Although anti-adhesion therapies are a novel mainstay in the treatment of inflammatory bowel diseases (IBDs), the mechanisms controlling integrin-dependent gut homing are poorly elucidated, and the available techniques for translational functional investigations are limited. Methods: We used dynamic adhesion assays to study adhesion of CD4+ T cells, CD8+ T cells, CD19+ B cells, and granulocytes to the addressins MAdCAM-1, VCAM-1, and ICAM-1. The effects of vedolizumab, natalizumab, etrolizumab-s, anti-CD11a, and anti-CD18 antibodies were explored. Results: Adhesion of peripheral blood leukocytes from IBD patients and control donors could be validly assessed, and integrin-mediated addressin adhesion could be specifically inhibited by anti-integrin antibodies. Numbers of adhering cells were partly, but not completely, related to integrin expression. Vedolizumab and etrolizumab-s resulted in similar reduction of adhesion to MAdCAM-1, and preliminary data proposed an association of dynamic adhesion to MAdCAM-1 with response to vedolizumab therapy. Conclusions: Dynamic adhesion assays are an easy and broadly applicable method for IBD research that is useful for future translational studies and potentially also for supporting clinical treatment decisions. 10.1093/ibd/izy077_video1izy077_Video_15786486962001.
EVALuna2:35167